(untitled) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2020)
This paper examines the impact of Netflix simultaneous release on the narrative structure of Mindhunter (2017- Today). The analysis of its first season shows that it adopts a structural model unconstrained by the procedural format formula, and that the season is conceived as a feature film that develops a complex main character. Simultaneous release impacts in cliffhangers and episodic plots too, as they become less prominent.